Intergenerational earnings mobility and the inheritance of employers - Miles Corak; Patrizio Piraino (Institute for the Study of Labor (IZA), 2010)
Our analysis of intergenerational earnings mobility modifies the Becker-Tomes model to incorporate the intergenerational transmission of employers, which is predicted to increase the intergenerational elasticity of earnings. About 6% of young Canadian men have the same main employer as their fathers but this is positively related to paternal earnings and rises discretely at the top of the distribution. We use a switching regression model and identify two regimes associated with the inheritance of employers that have different intergenerational earnings elasticities. The model also demonstrates that the inheritance of employers plays a role in understanding observed nonlinearities.
Keywords: J62; J64; J24; 330; Intergenerational mobility; job search; networks; Intergenerational Mobility; Soziale Mobilität; Einkommen; Arbeitsuche; Soziales Netzwerk; Familiensoziologie; Kanada